2020
DOI: 10.1093/botlinnean/boaa028
|View full text |Cite
|
Sign up to set email alerts
|

Leaf teeth in eudicots: what can anatomy elucidate?

Abstract: Leaf teeth are projections on the leaf blade margin. They are structurally variable, with characters that are important for taxonomy and phylogeny, but there is a paucity of information on the anatomy of these structures and little understanding of the features and their functions. Here we describe and compare the leaf tooth anatomy of 47 eudicot species. Toothed margin samples from leaves at different developmental stages were collected, fixed and studied under light and scanning electron microscopy. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
1
5
0
1
Order By: Relevance
“…Given that serrate leaves are a remarkable character for Ouratea [30], it seems reasonable to suppose that colleters, which occur at the apex of each marginal tooth, are a characteristic shared by several species of this genus. The report of marginal colleters in Luxemburgia, together with recent data showing a high correlation between leaf teeth and glands in eudicots [17], might corroborate this hypothesis.…”
Section: Anatomysupporting
confidence: 72%
See 2 more Smart Citations
“…Given that serrate leaves are a remarkable character for Ouratea [30], it seems reasonable to suppose that colleters, which occur at the apex of each marginal tooth, are a characteristic shared by several species of this genus. The report of marginal colleters in Luxemburgia, together with recent data showing a high correlation between leaf teeth and glands in eudicots [17], might corroborate this hypothesis.…”
Section: Anatomysupporting
confidence: 72%
“…Marginal glands, however, are commonly reported in Sauvagesia [ 15 , 27 , 28 ] and several additional genera of the subfamily Sauvagesioideae [ 14 ]. Recently, Rios et al [ 17 ] also demonstrated marginal colleters in two species of Luxemburgia . Nonetheless, data on the anatomy, ultrastructure, and secretory activity of these structures is lacking, and the present description appears to be unprecedented, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretory structures in leaf apexes or the tips of marginal teeth are not unusual, with records including extrafloral nectaries, hydathodes, and colleters [ 26 , 27 , 28 , 29 ]. Specifically, the presence of colleters in leaf apexes or marginal teeth is reported for Aquifoliaceae, Caryocaraceae, Celastraceae, Euphorbiaceae, Lechytidaceae, Ochnaceae, and Turneraceae [ 16 , 29 , 30 , 31 ], thus comprising a common position for foliar colleters. In Araceae, there is evidence of hydathodes at the leaf tip of Colocasia esculenta L. [ 4 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydathodes (i.e., hydathodes sensu stricto or epithemal hydathodes; for review see Cerutti et al, 2019) are often overlooked foliar structures that are relatively common among vascular plants, being responsible for the process of guttation (i.e., the exudation of apoplastic fluid; Bellenot et al, 2022). Marginal and apical hydathodes are the most prevalent (Cerutti et al, 2019; Jauneau et al, 2020; Rios et al, 2020), while laminar hydathodes, which are found over the entire leaf surface, seem to be restricted to Crassulaceae and three other eudicot families that have very few or no succulent representatives: Moraceae, Urticaceae and Myrothamnaceae (Chen & Chen, 2005; Drennan et al, 2009; Lersten & Curtis, 1991; Lersten & Peterson, 1974). The noteworthy anatomy of hydathodes in Crassula and their contrasting foliar distribution among different species have led to several exquisitely illustrated publications through the years (de Bary, 1884; Rost, 1969; Smirnova, 1973; Sporer, 1915; Voronin et al, 1976).…”
Section: Introductionmentioning
confidence: 99%